Biomechanical analysis for the IAAF World Championships London 2017 200 m Men's - Pollitt, L.; Walker, J.; Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
On Thursday 10th August, the men`s 200 m final was built-up around the ambitions of Wayde Van Niekerk to complete `the double` and the highly anticipated showdown with Botswana`s Isaac Makwala; the world leader with 19.77 s. It was also the first World Championship final not to feature Usain Bolt since 2003, and the elimination of Yohan Blake in the semi-finals meant there was no Jamaican representative. Bolt also lost one of his many records as Japan`s Abdul Hakim Sani Brown became the youngest men's 200 m finalist. Nevertheless, it was Ramil Guliyev, who, after leading into the home straight held off the field to win a time of 20.09 s; became his country`s first world gold medallist. It was also the first men`s 200 m final for 20 years not to feature a medallist from the USA or Jamaica. Van Niekerk, who only reached the final as the slowest nonautomatic qualifier (20.28 s), secured the silver medal by the smallest of margins crossing the line at 20.106 s just one thousandth of a second ahead of the 23-year-old Jereem Richards of Trinidad and Tobago. Richards, seventh entering the home straight, recorded the quickest second 100 m split (9.70 s) to push van Niekerk close. Great Britain`s 23-year-old Nethaneel Mitchell-Blake finished fourth in 20.24 s.